Socialization for Prevention of Diarrhea Diseas in Nitikan Village District, Plaosan District, Magetan - Hurip Jayadi; Poerwati, Sri; Sujangi, Sujangi; Sunaryo, Sunaryo; Indraswati, Denok; Prihastini, Lilis; Koesmantoro, Hery (Frontiers in Community Service and Empowerment, 2024)
Socialization is generally known as a learning process, this occurs because it is human nature that we will never be satisfied with something we don't know. This socialization is a form of effort to provide an explanation of an object that will be accepted by the subject. Socialization is usually carried out in an association agenda, whether formal or non-formal, so that socialization is considered very important for the community so that goals can be achieved. Based on preliminary information from the Plaosan Community Health Center, it is known that the highest incidence of diarrhea occurs in Nitikan Village. There were 12 cases of diarrhea in 2021, 15 in 2022 and 5 in January – April 2023. This research method uses lecture, question and answer, pre test, post test, demonstration methods. to society. The target of the socialization is 30 Nitikan Village Health cadres. Location of extension activities in Nitikan Village. The time for counseling/socialization is July 3 2023, at 09.00 – finish. The socialization officer is a lecturer at the Magetan Campus Sanitation Study Program and is assisted by students. From the results of counseling about diarrheal diseases to health cadres in Nitikan Village, Plaosan District, it was found that, their knowledge before the counseling was in the good category and after following the counseling was in the good category, meaning there was an increase in knowledge about diarrheal diseases.